Identification of the sucrose phosphate synthase (SPS) gene family reveals the positive role of NtSPS5 and NtSPS6 in drought stress tolerance of tobacco - Bingyu Li; Huan Su; Shuaibin Wang; Junping Gao; Zhong Wang; Jun Yang; Xin Xu (Chemical and Biological Technologies in Agriculture)
Abstract Background Sucrose phosphate synthase (SPS) is an important enzyme in the sucrose synthesis of plants, governing the accumulation and distribution of photosynthetic assimilates, which is essential for plant growth and stress tolerance. Results This study successfully identified eight NtSPS genes within the genome of cultivated tobacco. Phylogenetic analysis revealed that these genes are categorized into three subfamilies, a classification supported by the examination of their gene structures and conserved domains. The promoters of the NtSPSs contained a variety of cis-elements associated with plant development, responses to phytohormones, and stress resistance. Expression profiling demonstrated that NtSPS genes exhibit distinct expression patterns across different tissues and under various stress conditions. Notably, the majority of NtSPS genes, especially NtSPS5 and NtSPS6, showed high expression in leaves and increased expression in both roots and leaves following drought treatment. Furthermore, overexpression of NtSPS5 and NtSPS6 in tobacco plants significantly improved the germination rate under mannitol treatment and enhanced the activity of antioxidant enzymes along with chlorophyll fluorescence parameters under drought stress. These results suggest that NtSPS5 and NtSPS6 have a positive impact on drought stress tolerance in tobacco plants. Conclusions Therefore, this study provides the significant target in drought resistance breeding and lays the foundation for further investigation into the function and regulatory mechanisms of SPS genes. Graphical Abstract